Effect of warming on the carbon flux of the alpine wetland on the Qinghai–Tibet Plateau - Yasin, Adile; Niu, Bin; Chen, Zhengan; Hu, Yilun; Yang, Xiaoqin; Li, Yue; Zhang, Gengxin; Li, Fengjie; Hou, Weiguo (Frontiers in Earth Science, 2022)
Under the scenario of global warming, the response of greenhouse gas emissions from alpine wetlands remains unclear. In this study, fluxes of CO2 and CH4 were measured during daytime for the microtopographic features of hollows and hummocks in a wetland in the Tibetan Plateau under two elevated temperatures, increments of ∼1°C (T1 treatment) and ∼2°C (T2 treatment), during the growing season in 2019. The results showed that warming significantly increased the cumulative net ecosystem CO2 exchanges (NEE) for both microtopographic features in the wetland compared to the control due to a combination of the increased gross primary production (GPP) with an increase in ecosystem respiration (ER). Similarly, warming also increased cumulative CH4 emission significantly. The effect was stronger for T2 than that for T1 for all component fluxes (GPP, ER, NEE, and CH4). Generally, NEE and CH4 fluxes both rose at first and then decreased. NEE peaked at the end of July for both hollows and hummocks, while CH4 emissions peaked in the middle of August. The cumulative CH4 emissions from the hummocks were significantly higher than those of the hollows, and CH4 emissions under illumination were significantly higher than those in darkness, which may be caused by the irradiation-sensitive vegetable internal convective gas transport system which diffuses CH4 from the pedosphere. This study revealed that warming strengthened the function of the CO2 sink but also increased CH4 emissions from the alpine wetlands on the Qinghai–Tibet Plateau.